2012
DOI: 10.1143/jjap.51.10nc35
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Cu2SnS3Thin Films by Sulfurization of Cu/Sn Stacked Precursors

Abstract: Cu2SnS3 (CTS) has been reported to have various band gap energies in the range of 0.93–1.77 eV and an absorption coefficient of 1.0×104 cm-1. It consists of elements that are inexpensive due to their abundance in Earth's crust. Consequently, CTS is expected to be utilized in the absorber layers of thin-film solar cells. In this study, Cu/Sn stacked-layer thin-film precursors were deposited on glass and glass/Mo substrates by electron beam evaporation. CTS thin films were fabricated by sulfurizing the precursor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…The large series and small shunt resistance gives rise to a lower FF. The V OC was rather low given the band gap energy, which appears to be a common problem for CTS devices as compared to CIGS and/or CZTS-based devices [10][11][12][13][14][15][16]. The low value of V OC than E g indicates that the main recombination mechanism is band-to-band along with a recombination at deep traps within the band gap.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The large series and small shunt resistance gives rise to a lower FF. The V OC was rather low given the band gap energy, which appears to be a common problem for CTS devices as compared to CIGS and/or CZTS-based devices [10][11][12][13][14][15][16]. The low value of V OC than E g indicates that the main recombination mechanism is band-to-band along with a recombination at deep traps within the band gap.…”
Section: Resultsmentioning
confidence: 95%
“…They observed that the films obtained by the direct evaporation of the synthesized compound were copper deficient, while those grown in an atmosphere of copper vapor were observed to be more stoichiometric. Over the past half-decade, CTS thin films have been synthesized by various techniques such as evaporation [11,12], electro-deposition [13,14], screen printing [15], spin coating [16], solution based colloidal methods [17], etc. Up to now, the efficiency of CTS-based solar cells is quite low compared with its quaternary counterparts and thus it needs more systematic studies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this properties, this material has an advantage on the environmental pollution issue since it is chemically stable and has no highly toxic elements composed in it. However, the researches concerning with this CTGS alloy in the thin-film photovoltaic applications are still in the early initial phase and the study on CTGS alloy itself with various Ge contents is still premature compared to the study of individual Cu 2 SnS 3 (CTS) or Cu 2 GeS 3 (CGS) ternary compounds [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32]. Up to now, only a few reports about the photovoltaic devices based on the CTGS with various Ge contents have been made [12,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there were lots of reports on CTS thin film solar cells by several research groups using different approaches, including sputtering [2, 6 7], evaporation [8,9], successive ionic layer adsorption and reaction (SILAR) [10], electrodeposition [11], solid reactions [3,12,13], spray pyrolysis [14], and solvothermal synthesis [15]. However, it is quite difficult to obtain CTS thin film solar cells with high conversion efficiencies by experiments.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is quite difficult to obtain CTS thin film solar cells with high conversion efficiencies by experiments. At present, the highest conversion efficiency of the CTS solar cell reported is 2.92% [8,9,11,[16][17][18][19]. The prevalent low efficiencies can be attributed to various sources, such as bulk material impurities and defects, M a n u s c r i p t interface trap states, and notably unfavorable heterojunction band alignment [20].…”
Section: Introductionmentioning
confidence: 99%